2019
DOI: 10.11606/issn.1678-4456.bjvras.2019.146687
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of feline immunodeficiency virus and feline leukemia virus in domestic cats of Fortaleza, Ceará

Abstract: Feline Immunodeficiency Virus (FIV) and Feline Leukemia Virus (FeLV) are important etiologic agents of immunosuppressive diseases in felines. The objective of the present study was to determine the prevalence of these retroviruses in domestic cats in Fortaleza, Ceará and the epidemiological factors associated with these infections. Between 2015 and 2016, 138 blood samples were collected and tested for FIV and FeLV by the enzyme immunoadsorption assay (ELISA). Parameters such as breed, gender, age, reproductive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
1
2
0
3
Order By: Relevance
“…[17] The prevalence of FeLV infection observed in the current study (Fig. 1) was similar to the results of studies from Italy [52,41], Austria [44], Poland [30], Cyprus [46], Israel [5], Brazil [51], and Mexico [42] (Table 2). In the current study, the FeLV prevalence was higher than observed in Ireland [17], Germany [18], Serbia [19], Switzerland [48], USA and Canada [16], Japan [31], Thailand [49], Australia [12], and New Zealand [47], but lower than in Hungary [8], Turkey [1,29], Malaysia [50,9], Iran [43], and China [45] (Table 2).…”
Section: Discussionsupporting
confidence: 89%
“…[17] The prevalence of FeLV infection observed in the current study (Fig. 1) was similar to the results of studies from Italy [52,41], Austria [44], Poland [30], Cyprus [46], Israel [5], Brazil [51], and Mexico [42] (Table 2). In the current study, the FeLV prevalence was higher than observed in Ireland [17], Germany [18], Serbia [19], Switzerland [48], USA and Canada [16], Japan [31], Thailand [49], Australia [12], and New Zealand [47], but lower than in Hungary [8], Turkey [1,29], Malaysia [50,9], Iran [43], and China [45] (Table 2).…”
Section: Discussionsupporting
confidence: 89%
“…FIV prevalence varies from 3.6% in North America and 3.2-6.6% in Europe (Gleich et Biezus et al 2019). FeLV prevalence of 10.6%, was twice the prevalence found in the city of Fortaleza (5.8%) and much higher than the prevalence found in other northeastern states, which vary from 0.6% in Rio Grande do Norte to 3.0% in Bahia (Martins et al 2015; Barros et al 2017;Lacerda et al 2017;Rocha et al 2019). These data suggest a greater spread of this virus in Jericoacoara Village compared to other cities in the Northeast, since in most other studies the animals studied were cats treated in veterinary clinics and hospitals, which are more likely to be infected with the virus.…”
Section: Discussionmentioning
confidence: 61%
“…Tal variável está diretamente ligada aos protocolos clínicos seguidos pelo serviço de atendimento em questão, onde a castração é preconizada nos pacientes atendidos, tendo em vista que o acasalamento é uma das formas de transmissão dos retrovírus. Além disso, muitos animais que haviam sido testados já eram castrados o que não pode descartar a possibilidade da infecção ter ocorrido antes do procedimento cirúrgico de esterilização (BIEZUS et al, 2018;ROCHA et al, 2019).…”
Section: Anounclassified
“…FeLV, em que a idade prevalente encontrada porRocha et al (2019) foi de 1-5 anos. Em Goiás, o estudo elaborado porLemos et al (2019) demonstrou dados semelhantes, com ocorrência de animais de 1-6 anos com FIV.Westman et al (2016) relatam que tanto animais idosos quanto jovens estão suscetíveis a infecção por FeLV, porém o fato de ter idosos positivos levanta algumas questões como a idade em que se contaminaram, se a contaminação ocorreu por um contactante, tendo em vista que a expectativa de vida de um gato FeLV positivo é de 2 anos (MEGID et al, 2018) ou o vírus ficou latente e só agora reativou.…”
unclassified
See 1 more Smart Citation